Physical interpretation of passive mass transfer coefficients as friction coefficients - Gordiyenko, O. I.; Gordiyenko, E. O. (Biophysical Bulletin, 2018)
To interpret results on passive transmembrane mass transfer one utilize often the relationships between standard transport characteristics of biological membranes and coefficients of reciprocal friction between separate components of a system. In contrast to Kedem and Katchalsky, obtained the correlation between transport characteristics of biological membranes and friction coefficients when considering the one-dimensional diffusion via plane unbounded immobile separately permeable membrane, this work presents the firstly obtained analogous correlation for the case of closed mobile separately permeable membrane of unrestricted shape, that reflects more adequately the real state when studying the processes of mass transfer via cell membranes.